Base-station selection in cooperative single frequency cellular network - Kamoun, M.; Mazet, L. (2007 IEEE 8th Workshop on Signal Processing Advances in Wireless Communications, 2007)
Single frequency cellular network (SFCN) combined with virtual MIMO (VMIMO) and cooperation is a novel and competitive deployment which allows a more efficient spectrum usage for the next generation wireless networks. However, for uplink transmission, cooperative techniques induce a large amount of data to be transmitted on the backhaul of the infrastructure. In order to reduce the backhaul load we want to select for each user only a small number of decoding base- stations. This contribution presents two possible selection algorithms: the first is based on genetic approach and the second is inspired from the sphere decoder. Both are compared with classical selection techniques: SNR sort and exhaustive search.